Penerapan Gamifikasi Adaptif Terhadap Pengembangan Berpikir Kreatif Matematis Ditinjau dari Gaya Kognitif - Bilqisthi, Nadaina; Faridah, Luluk; Haryono, Heny Ekawati (Indo-MathEdu Intellectuals Journal, 2025)
Mastery of concepts and creative thinking in problem-solving can be facilitated through gamification. This study aims to describe the mathematical creative thinking abilities of students at SMK Darul Ma’wa Plandirejo on the topic of probability using a gamification-based approach, viewed from the cognitive styles of Field Independent (FI) and Field Dependent (FD). A descriptive qualitative method was employed. Research instruments included a creative thinking test, gamified learning via Kahoot and Google Form, and semi-structured interviews based on Munandar’s indicators of creative thinking: fluency, flexibility, originality, and elaboration. The findings show that students with an FI cognitive style outperformed FD students across all indicators—fluency, flexibility, elaboration, and originality. In contrast, FD students demonstrated more varied results but did not exceed the performance of FI students. This study presents a novel finding that gamification through Kahoot can enhance student motivation and engagement in the learning environment. Furthermore, it highlights significant implications for teachers in designing appropriate, adaptive, and innovative technology-based learning to meet the diverse cognitive styles of students.